The Effect of Weaving Activities on Fine Motor Skills of 5-6 Year Old Children at Ra Al Inayah Klambir Lima - Sari, Fika Wulan; Simaremare, Aman (Jurnal Pendidikan Rafflesia, 2023)
This study aims to describe the effect of weaving activities on fine motor skills of children aged 5-6 years at RA Al Inayah Klambir Lima. This type of research is experimental, using a pre-experimental research design using a one group pretest-posttest design. The population in this study was the entire group of children aged 5-6 years at RA Al Inayah Klambir Lima with 15 students. The sample used in this study used saturated samples, meaning that all populations were sampled, totaling 15 children. Data collection techniques using observation. Data were analyzed using descriptive statistical techniques and the Wilcoxon test, which was continued with a significance test at 0.025. The results showed that the average value before the weaving activity (pre test) was categorized as sufficient with an average score = 1.82, while after the weaving activity (post test) was categorized as very good with an average score = 3.45. The results of the Wilcoxon test show the value of Whitung = 120> Wtabel = 25, because Whitung> Wtabel, Ho is rejected and Ha is accepted. Thus it is stated that weaving activities have a significant influence on the fine motor skills of children aged 5-6 years at RA Al Inayah Klambir Lima.